Nakhon Pathom community development strategies: implication on building community capability for product development among small and micro community enterprise / Mohamed Samsudeen Sajahan and Nur Zainie Abd Hamid - Sajahan, Mohamed Samsudeen; Abd Hamid, Nur Zainie (2019)
Cultivating capability is regarded as an important tool for successful execution and sustainability of product development among local community (Laverack & Thangphet, 2009; Aref, Redzuan, & Gill, 2010; Laverack, 2006; Gibbon, Labonte, & Laverack, 2002). There is a considerable body of literature that suggest the importance of identifying priorities and opportunities in building community capabilities for development (Victurine, 2000) and as well discusses approaches for its implementation and evaluation (Goodman et al., 1998; Hawe et al., 2000; Labonte and Laverack, 2001; Gibbon, Labonte and Laverack, 2002). Assessment of the implementation or evaluation on building community capability is regarded as essential to serve a meant in scrutinising project a achievement; lead to a better demonstration to policy maker about changes within their communities and also to access future project funds.